1998
DOI: 10.1007/bf02467641
|View full text |Cite
|
Sign up to set email alerts
|

Capillary electrophoretic study of the complexation of nucleotides with magnesium and calcium ions

Abstract: SummaryThe complexation equilibrium between nucleotides (ATP, ADP) and inorganic cations (Mg 2+, Ca 2+) has been studied by capillary electrophoresis. The equilibrium constant and the stoichiometry of nucleotideinorganic cation complexes can be deduced from the dependence of the electrophoretic mobility of each nucleotide on the negative logarithm of the inorganic cation concentration. The experimental values of complexation constants determined by CE compare favorably with those in the literature. As expected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Cahours et al [6][7][8] reported the addition of inorganic cations to the buffer could improve the resolution of nucleotide mono-, di-and triphosphates in CZE separation [6][7][8]. In this work, either magnesium chloride or zinc acetate was tested to see whether the resolution of UMP isomer would be improved.…”
Section: Interaction Of Nucleotides With Metal Ionsmentioning
confidence: 94%
See 1 more Smart Citation
“…Cahours et al [6][7][8] reported the addition of inorganic cations to the buffer could improve the resolution of nucleotide mono-, di-and triphosphates in CZE separation [6][7][8]. In this work, either magnesium chloride or zinc acetate was tested to see whether the resolution of UMP isomer would be improved.…”
Section: Interaction Of Nucleotides With Metal Ionsmentioning
confidence: 94%
“…The method appears to be very effective to resolve all 12 nucleotide isomers in less than 15 min. Cahours et al [6][7][8] have studied the complexation equilibrium between nucleotides and inorganic cations (Mg 21 , Ca 21 , Cd 21 , and Zn 21 ) by CE. These studies would be useful for optimization of the separation of nucleoside mono-, di-and triphosphates by CE according to their different affinity for inorganic cations added to the buffer.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been reported several times in the literature [25][26][27][28][29] as Mg 2+, Ca 2+, Zn 2+, Mn 2+, Cd2+...) and nucleotides or nucleic acids and reported an affinity scale of metal ions versus phosphate groups and bases of nucleotides.…”
Section: Addition Of a Complexing To The Buffer (Cadmium Ion)mentioning
confidence: 99%
“…Some workers used MEKC to separate nucleotides [19,[23][24][25]. Other approaches derived benefit from the complexation of nucleotides with transient metals for better resolution [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%